Distinct forebrain regions define a dichotomous astrocytic profile in multiple system atrophy - Schneider, Yanni; Gauer, Lisa Carina; Andert, Marie; Hoffmann, Alana; Riemenschneider, M. J.; Krebs, W.; Chalmers, Nicholas; Lötzsch, C.; Naumann, Ulrike; Xiang, Wei; Rothhammer, Veit; Beckervordersandforth, Ruth; et al. (Acta Neuropathologica Communications, 2024)
The growing recognition of a dichotomous role of astrocytes in neurodegenerative processes has heightened the need for unraveling distinct astrocytic subtypes in neurological disorders. In multiple system atrophy (MSA), a rare, rapidly progressing atypical Parkinsonian disease characterized by increased astrocyte reactivity. However the specific contribution of astrocyte subtypes to neuropathology remains elusive. Hence, we first set out to profile glial fibrillary acidic protein levels in astrocytes across the human post mortem motor cortex, putamen, and substantia nigra of MSA patients and observed an overall profound astrocytic response. Matching the post mortem human findings, a similar astrocytic phenotype was present in a transgenic MSA mouse model. Notably, MSA mice exhibited a decreased expression of the glutamate transporter 1 and glutamate aspartate transporter in the basal ganglia, but not the motor cortex. We developed an optimized astrocyte isolation protocol based on magnetic-activated cell sorting via ATPase Na+/K+ transporting subunit beta 2 and profiled the transcriptomic landscape of striatal and cortical astrocytes in transgenic MSA mice. The gene expression profile of astrocytes in the motor cortex displayed an anti-inflammatory signature with increased oligodendroglial and pro-myelinogenic expression pattern. In contrast, striatal astrocytes were defined by elevated pro-inflammatory transcripts accompanied by dysregulated genes involved in homeostatic functions for lipid and calcium metabolism. These findings provide new insights into a region-dependent, dichotomous astrocytic response—potentially beneficial in the cortex and harmful in the striatum—in MSA suggesting a differential role of astrocytes in MSA-related neurodegenerative processes.
CRIS-Team Scopus Importer:2024-01-12

The astrocyte-produced growth factor HB-EGF limits autoimmune CNS pathology - Linnerbauer, Mathias; Lößlein, Lena; Vandrey, Oliver; Peter, Anne; Han, Yanan; Tsaktanis, Thanos; Wogram, Emile; Needhamsen, Maria; Kular, Lara; Nagel, Lisa; Zißler, Julia; Andert, Marie; et al. (Nature Immunology, 2024)
Central nervous system (CNS)-resident cells such as microglia, oligodendrocytes and astrocytes are gaining increasing attention in respect to their contribution to CNS pathologies including multiple sclerosis (MS). Several studies have demonstrated the involvement of pro-inflammatory glial subsets in the pathogenesis and propagation of inflammatory events in MS and its animal models. However, it has only recently become clear that the underlying heterogeneity of astrocytes and microglia can not only drive inflammation, but also lead to its resolution through direct and indirect mechanisms. Failure of these tissue-protective mechanisms may potentiate disease and increase the risk of conversion to progressive stages of MS, for which currently available therapies are limited. Using proteomic analyses of cerebrospinal fluid specimens from patients with MS in combination with experimental studies, we here identify Heparin-binding EGF-like growth factor (HB-EGF) as a central mediator of tissue-protective and anti-inflammatory effects important for the recovery from acute inflammatory lesions in CNS autoimmunity. Hypoxic conditions drive the rapid upregulation of HB-EGF by astrocytes during early CNS inflammation, while pro-inflammatory conditions suppress trophic HB-EGF signaling through epigenetic modifications. Finally, we demonstrate both anti-inflammatory and tissue-protective effects of HB-EGF in a broad variety of cell types in vitro and use intranasal administration of HB-EGF in acute and post-acute stages of autoimmune neuroinflammation to attenuate disease in a preclinical mouse model of MS. Altogether, we identify astrocyte-derived HB-EGF and its epigenetic regulation as a modulator of autoimmune CNS inflammation and potential therapeutic target in MS.
CRIS-Team Scopus Importer:2024-03-08

Vimentin network dysregulation mediates neurite deficits in SNCA duplication Parkinson’s patient–derived midbrain neurons - Schneider, Yanni; Koller, Aron; Schweigert, Alina; Andert, Marie; Hoffmann, Laura; O’Brien, Sydney; Seebauer, Lukas; Plötz, Sonja; Kielkowski, Pavel; Winkler, Jürgen; Schlachetzki, Johannes C.M.; Xiang, Wei (Science Advances, 2025)
Duplication of the SNCA gene (SNCADupl), linked to elevated levels of α-synuclein (aSyn), is a genetic cause of Parkinson’s disease (PD). Our prior work with human-induced pluripotent stem cell (hiPSC)–derived midbrain neurons generated from patients with PD SNCADupl identified neuritic deficits, accompanied by decreased levels of cytoskeletal element β-tubulin-III (bTubIII). To explore mechanisms underlying these effects in SNCADupl neurons, we used CRISPR-Cas9 to generate isogenic control hiPSCs. Isogenic correction of SNCA dosage restored SNCADuplinduced neurite defects and bTubIII levels. Multi-omics analyses revealed SNCADupl-induced alterations in neuronal differentiation, with a notable down-regulation of PAX6. Moreover, SNCADupl induced an up-regulation of vimentin. Further characterization revealed heightened vimentin truncation associated with altered distribution and organization. Similar changes in vimentin levels and truncation were observed in postmortem putamen tissue from patients with sporadic PD. Notably, targeting vimentin with okadaic acid and withaferin A restored bTubIII- and neurite-associated defects, suggesting its potential to prevent aSyn-mediated neuritic degeneration.
CRIS-Team Scopus Importer:2025-06-27